2008
DOI: 10.1002/ajh.21211
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic features of plasmacytomas: A multicenter study of Turkish Oncology Group‐Sarcoma Working Party

Abstract: To identify the outcomes of prognostic factors of solitary plasmacytoma mainly treated with local radiotherapy (RT). The data were collected from 80 patients with solitary plasmacytoma (SP). Forty patients (50.0%) received radiotherapy (RT) alone while 38 of them (47.5%) were treated with surgery (S) and RT. The median radiation dose was 46 Gy (range 30-64). The median follow up was 2.41 years (range 0.33-12.33). Ten-year overall survival (OS) and local relapse-free survival (LRFS) were 73% and 94%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 40 publications
4
54
1
1
Order By: Relevance
“…The median TTP in this cohort was 49 months (18 months in those who progressed), and this along with the overall proportion of patients progressing is broadly comparable with previous series. [3][4][5][6][7][8][9][10] Progression was documented in 72% (26/34) of patients with OMD compared with 12.5% (2/16) without, and the median TTP was 26 months vs not reached (NR) (P 5 .003; Figure 1A). In a similar analysis, Warsame et al have demonstrated that the presence of clonal plasma cells (as determined by trephine biopsy immunohistochemistry), but below the 10% threshold for the diagnosis of myeloma, was associated with progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median TTP in this cohort was 49 months (18 months in those who progressed), and this along with the overall proportion of patients progressing is broadly comparable with previous series. [3][4][5][6][7][8][9][10] Progression was documented in 72% (26/34) of patients with OMD compared with 12.5% (2/16) without, and the median TTP was 26 months vs not reached (NR) (P 5 .003; Figure 1A). In a similar analysis, Warsame et al have demonstrated that the presence of clonal plasma cells (as determined by trephine biopsy immunohistochemistry), but below the 10% threshold for the diagnosis of myeloma, was associated with progression.…”
Section: Resultsmentioning
confidence: 99%
“…The overall incidence of progression is 37% to 72%, with median reported times to progression (TTP) of 2 years or less. [3][4][5][6][7][8][9][10] We hypothesized that progression in SPB might occur as a result of occult disease outside of the irradiation field. To further evaluate this, we used multiparameter flow cytometry (MFC) to assess staging bone marrow (BM) samples for the presence of occult disease and determine its impact on outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rarity, most of our knowledge derives from retrospective studies, which usually regard RT as the most effective therapy. After a moderate (40-50Gy) dose of radiation (Mendenhall et al, 1980;Mendenhall et al, 2003;Kilciksiz et al, 2008), a 5-year local control rate of 81-95% could be expected (Ozsahin et al, 2006;Sasaki et al, 2012;Suh et al, 2012). 5-year overall survival rate is reported to be 70-78% (Frassica et al, 1989;Reed et al, 2011;Suh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As they considered, close observation is preferred rather than adjuvant RT after R0 resection (Strojan et al, 2002). Interestingly, a research including 57 SBPs and 23 EMPs showed surgery+RT resulted in significantly longer PFS, compared with RT alone (median PFS 7.4 years vs 2.6 years) (Kilciksiz et al, 2008). But this conclusion should be interpreted in caution because EMP, which has a better prognosis intrinsically, is usually associated with a higher portion of excisional biopsy due to its derivation from soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation